Using of Different Satellite-Derived Indices to Detect the Spatiotemporal Changes of the Al-Razzaza Lake, Iraq - Al-lami, Ahmed Kadhim; Abbood, Raad A.; Al Maliki, Ali A.; Hussain, Hussain M.; Alabidi, Abdulkadhim J. (Iraqi Journal of Science, 2023)
Remote sensing and GIS applications (Geoinformatics tools) involve a wide range of techniques for providing a solution for future water resources management and offer an excellent means to improve knowledge of sustainable planning. Al-Razzaza is the second largest lake in Iraq; it is a common source of fishery fortune and floodwater reservoir in southwestern Iraq. In recent years, the lake faced a noticeable amount of desiccation, which is considered a threat to the biodiversity and wildlife of the lake. The study aimed to detect the Lake’s spatiotemporal changes from 1988 to 2018. Multi satellite-derived indices were investigated for the extracting of the lake water body. Results showed that the lake volume decreased by about 30% from 1990-2002, while it was about 70% from 1990-2014. A slight rise in the lake area was recorded in 2016 by about 40% compared with 2014. The accurate measurement was achieved to find a method showing the spatiotemporal aspects of lake changes.